2015
DOI: 10.26477/idj.v37i1.34
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Surface Roughness of Cross Linking Acrylic Resin Processed by Different Heat Curing Methods

Abstract: Background: Heat-cured acrylic resin is considered one of the most commonly used denture base material in denture construction, but this material is not ideal in every respect. So many researches have been carried out to find an alternative material like cross linking acrylic resin. Meanwhile, the curing procedures have been modified to improve the physical and mechanical properties of resin materials .The aim of this study was to evaluate the effect of three curing methods:(water bath, autoclave short cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The improvement in Ra values could be attributed to the levels of heat and pressure during autoclave polymerization, where the increase in the degree of conversion reduced the residual monomer and also improved surface roughness 31) . Autoclave polymerization significantly showed a lower Ra value in comparison to the control group, which was in agreement with previous research 32) . However, this study's findings were in disagreement with Nazhat et al 33) who found that there were no significant differences between the autoclave polymerization and the water bath methods.…”
Section: Discussionsupporting
confidence: 93%
“…The improvement in Ra values could be attributed to the levels of heat and pressure during autoclave polymerization, where the increase in the degree of conversion reduced the residual monomer and also improved surface roughness 31) . Autoclave polymerization significantly showed a lower Ra value in comparison to the control group, which was in agreement with previous research 32) . However, this study's findings were in disagreement with Nazhat et al 33) who found that there were no significant differences between the autoclave polymerization and the water bath methods.…”
Section: Discussionsupporting
confidence: 93%
“…For enhancement in its mechanical properties, researchers have amalgamated additives such as glass fibers, carbon fibers, rubber graft copolymer and polyethylene in its composition [3]. Along with additives, different types of equipment have also been used for processing of PMMA in an attempt to improve its strength, but none of them have been shown to be superior to the other [9][10][11]. To enhance the properties of strength.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for denture processing include water bath (WB), air circulating oven (ACO) and dry heat oven (DHO). WB is commonly used for denture base processing due to its ease of handling and cost effectiveness [11,19,20]. While DHO is also used for curing heat cure acrylic resin that showed improved dimensional stability, but less common due to its equipment cost and efficiency [21].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional water bath method (short polymerization cycle) was used for the control group due to the common use of this method among labs and its simplicity. This method was used by many previous researchers and considered as a control method in the polymerization of the acrylic dentures [15][16][17][18][20][21][22][23][24][25][26]. The polymerization using the autoclave technique was used previously by several researchers [15][16][17]22].…”
Section: Discussionmentioning
confidence: 99%